ANALISIS NILAI – NILAI PENDIDIKAN KARAKTER DALAM FILM UPIN DAN IPIN PRODUKSI LES COPAQUE TAHUN 2010 - Purnomo, Fazrul Sandi (UNIB Press, 2016)
The purpose of this study to determine the values of character education in the film of Upin and Ipin production Les' Copaque in 2010. This research uses descriptive method. The data in this research is the dialogue in the film of Upin and Ipin production in 2010 that contains the value of character education. Based on the analysis found values contained in the film of Upin and Ipin production Les' Copaque in 2010 is religious, honest, tolerance, discipline, hard work, creative, curiosity, appreciate the achievements, friendly, social care / care about others, responsibility, brave, cooperation, mutual help, wisdom, respect for all life forms and environment that care of each other, respect for others / public politeness, and self-respect. There is value that specially treated is patriotism because it involves nationalism. Upin and Ipin Film production of Les Copaque in 2010 containing values of character education.